x^3+2x-x-2=0

Substitute with 1:

1+2-1-2=0

Then 1 is one of the function's roots.

Then (x-1) is one of the factors.

Now divide the function by (x-1).

x^3+2x-x-2=0

(x-1)(x^2+3x+2)=0

Factorize:

(x-1)(x+1)(x+2)=0

Then the roots are:

x1=1

x2=-1

x3=-2

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now